Thrombosis of the brachial artery – a rare and devastating complication after a simple closed posterolateral elbow dislocation - Masionis, Povilas; Bobina, Rokas; Uvarovas, Valentinas; Porvaneckas, Narūnas; Šatkauskas, Igoris (Acta medica Lituanica, 2020)
Dislocation of the elbow joint is the second most common dislocation after the shoulder joint. Although this pathology is relatively common, concomitant vascular injuries are rare. We present a case of a patient who sustained a fall on his arm with an outstretched elbow that resulted in a closed simple posterolateral elbow dislocation and delayed thrombosis of the brachial artery followed by two revascularisation surgeries. The physician must always maintain a high index of suspicion for a concomitant vascular injury before and after closed reduction of the elbow joint and have in mind that complete ischemia without any pulsations could be absent because the elbow is surrounded by rich collateral anastomoses. Suspicion should be even stronger in the presence of bony lesions or open injuries. A team of trauma and vascular surgeons has to work hand in hand as surgical treatment with a saphenous graft or direct suture is the first method of choice with the prior requirement of a stable elbow joint.